Parenteral nutrition compatibility and stability: A comprehensive review. Issue 2 (3rd January 2022) - Boullata, Joseph I.; Mirtallo, Jay M.; Sacks, Gordon S.; Salman, Genene; Gura, Kathleen; Canada, Todd; Maguire, Angela; ,
Abstract: Several guidance documents support best practices across the stages of the parenteral nutrition (PN) use process to optimize patient safety. The critical step of PN order verification and review by the pharmacist requires a contextual assessment of the compatibility and stability implications of the ordered PN prescription. This article will provide working definitions, describe PN component characteristics, and present a wide‐ranging representation of compatibility and stability concerns that need to be considered prior to preparing a PN admixture. This paper has been approved by the American Society for Parenteral and Enteral Nutrition (ASPEN) Board of Directors.